(untitled) (Ukrainian Journal of Ophthalmology, 2025)
Background: The prevalence of tick borne borreliosis has increased significantly in recent years. There have been reports on conjunctivitis, anterior uveitis, optic neuritis and other inflammatory eye diseases caused by Borrelia species. Case: This case of successful treatment of focal chorioretinitis caused by Borrelia burgdorferi/Toxoplasma gondii co-infection indicates that elucidating etiology and administering etiological therapy are essential for successful treatment outcomes. Discussion: Since there are few reports in the literature describing the ocular manifestations of Lyme disease, borreliosis is infrequently suspected by ophthalmologists as an etiologic factor in the development of inflammatory eye disease. Consequently, an enzyme immunoassay for Borrelia burgdorferi is not used in a routine diagnostic evaluation of patients with inflammatory eye disease. Conclusion: Specific Borrelia burgdorferi antibody serology is required to elucidate the etiology of ocular inflammation if a patient has a history of tick bites even in the absence of symptoms of Lyme disease. In addition, one should take in account that ocular infections are frequently mixed in nature.